Pemphigus and pemphigoid research by dermatologists and stomatologists: A scientometric and comparative study - Shanxin Zhou; Qianqian Zhang; Yiwen Deng; Zhengyu Shen; Wei Liu (Elsevier, 2023)
Background/purpose: Pemphigus and pemphigoid are systemic bullous autoimmune diseases affecting skin and/or mucosal membranes with the life-threatening nature, especially pemphigus vulgaris. The papers published by dermatologists and stomatologists preferentially represent their concerns of a mucocutaneous disease. Materials and methods: The objective of this study was to compare the scientometric characteristics of pemphigus and pemphigoid publications by dermatologists and stomatologists in the Scopus database. Results: There are 9276 and 760 papers published by dermatologists and stomatologists, respectively. The annual number of the publications by dermatologists stably raised from 218 to 526 during 2007-2022; while the number by stomatologists raised with a small amount from 18 to 51 during this period. For the most-cited top-200 papers, the total citation count is 42,766 and the h index is 148 for pemphigus publications by dermatologists; whereas the count is 14,689 and h index is 63 for publications by stomatologists. Notably, first signs of pemphigus often appear in oral mucosa, manifesting as erythema, blisters, as well as mouth ulcer, gingivitis, lichen planus-like pemphigus. Conclusion: This study firstly reports the scientometric characteristics of pemphigus publications by dermatologists and stomatologists. The scale and citations of dermatologists' publications greatly outweigh stomatologists' ones, suggesting stomatologists can learn from and more cooperate with dermatologists regarding pemphigus research.